Kinetics of Naphthalimide Aminolysis - Mitchell, Stanford D.; Anderson, Samantha M. (My University, 2015)
We have carried out kinetic studies using triethylamine as the base solvent in order to determine the kinetic order of the reaction with respect to the butylamine. The purpose of this study was to test the hypothesis that the reaction may be subject to general base catalysis.
Color poster with text and images.
Keywords: Chemistry; Kinetics; Naphthalimide aminolysis; Posters